The Effect of Digital Literacy, Parental Involvement, Religious Learning Environment, and Teaching Methods on Students’ Achievement in Islamic Education - Huzma Juliantri (Journal Management & Economics Review (JUMPER), 2026)
This study aims to examine the effect of digital literacy, parental involvement, religious learning environment, and teaching methods on students’ achievement in Islamic education. Employing a quantitative explanatory research design, data were collected from 250 students enrolled in Islamic education subjects through structured questionnaires and academic documentation. The data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results indicate that digital literacy, parental involvement, religious learning environment, and teaching methods each have a positive and significant effect on students’ academic achievement. Simultaneously, these variables explain 53.9% of the variance in students’ achievement. Among the independent variables, the religious learning environment has the most dominant influence, followed by parental involvement, teaching methods, and digital literacy. These findings suggest that students’ academic success in Islamic education is shaped by an integrated ecosystem that combines technological competence, family engagement, supportive spiritual climate, and effective pedagogical strategies. The study highlights the importance of strengthening digital skills while maintaining value-based educational environments to enhance academic outcomes in Islamic education institutions.